Enhancing Work Engagement Through Glass Ceiling and Professional Self-Efficacy : The Mediating Role of Sustainable Career Development - Hapsari Pradana Iswari; Mafizatun Nurhayati (Asean International Journal of Business, 2026)
Purpose – This study aims to investigate the influence of Glass Ceiling and Professional Self-Efficacy on Work Engagement, with Sustainable Career Development as a mediating variable, among female staff-level civil servants at the Ministry of Industry, Republic of Indonesia.Methodology/approach – A quantitative approach was employed using a survey method. Data were collected from 114 female employees through validated questionnaires. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS).Findings – The results show that Glass Ceiling has a significant negative effect on Sustainable Career Development but does not directly influence Work Engagement. In contrast, Professional Self-Efficacy positively and significantly affects both Sustainable Career Development and Work Engagement. Furthermore, Sustainable Career Development is proven to mediate the effect of Professional Self-Efficacy on Work Engagement but does not mediate the effect of Glass Ceiling.Novelty/value – This study contributes to the literature by examining the integrated influence of gender-based career barriers and psychological resources on Work Engagement in the public sector. Its novelty lies in positioning Sustainable Career Development as a mediating variable—an area rarely explored in studies involving female civil servants. The findings offer new insights into how organizational and personal factors jointly shape employee engagement in bureaucratic settings.